Juridical Analysis of Decision No. 337/Pid.Sus/2020/PN. Jkt.Sel in the Perspective of Money Laundering and the Criminal Code - Hosnah, Asmak Ul; Djakarsih Putro, Sapto Handoyo; Jevis, Weldy; Prihatini, Lilik; Sinaga, Walter Aaron Life; Zacharias, Vasco Javarison; DRD, Moch Ilham (PALAR (Pakuan Law review), 2025)
Abstract  The purpose of this legal research is to elaborate and explain fundamentally the judge's legal considerations in Decision Number 337/Pid.Sus/2020/PN. Jkt.Sel related to the application of the provisions of the Money Laundering Crime (TPPU) and its relation to the Criminal Code (KUHP). Based on the verdict, the defendant Ir. Roni Wijaya was proven to have legally committed a tax crime as stipulated in Article 39A letter a of Law Number 28 of 2007 jo. Article 64 paragraph (1) of the Criminal Code and the crime of money laundering as stipulated in Article 3 of Law Number 8 of 2010. This type of research is a normative legal research that is descriptive and analytical, with a statutory approach and a case approach, using secondary data through literature studies and qualitative analysis. The results of the study show that the application of the TPPU article in this decision has reflected the double track system of criminality, where the predicate crime in the form of tax violations is the basis for proving TPPU. The merging of the provisions of the Anti-Corruption Law and the Criminal Code shows the application of the principle  of lex specialis derogat legi generali in criminal law. Thus, this decision affirms the consistency of the application of the law to economic crimes that have a systemic impact on state finances. Keywords: Money Laundering Crime, Decision Number: 337/Pid.Sus/2020/PN. Jkt.Sel, Criminal Code.